Implementation of Buteyko Breathing Technique in Nursing Care for Bronchial Asthma Patients: A Case Study - Zahirah, Beladinna Zalfa; Daniati, Eva (CV. Literasi Publikasi Indonesia, 2024)
The human respiratory system functions to obtain oxygen from the environment and expel carbon dioxide through the lungs. One common respiratory disorder is bronchial asthma, which can obstruct the airways. A non-pharmacological intervention for asthma patients is the Buteyko breathing technique. This study aims to analyze nursing care through the application of the Buteyko breathing technique in a patient diagnosed with bronchial asthma. A descriptive case study approach was used with one respondent and a literature review. Based on the assessment of Mr. H, the primary nursing problem identified was ineffective breathing pattern. The intervention, based on Evidence-Based Practice, involved performing the Buteyko breathing technique once a day for 15-20 minutes over 3 consecutive days. Results showed improvement: the respiratory rate decreased from 25 breaths/min to 21 breaths/min, oxygen saturation increased from 92% to 96%, and symptoms such as nasal flaring, chest retractions, and use of accessory muscles resolved. Nursing evaluation indicated the problem was resolved, evidenced by the improvement in the breathing pattern. In conclusion, the Buteyko breathing technique positively affects ineffective breathing patterns in Mr. H. It is recommended that the Buteyko breathing technique be considered as a non-pharmacological intervention for patients with bronchial asthma.